A historical study of the Iraqi national team’s participation in the blind men’s goalball in the Asian Championships for the period (2014-2022) - M. saja Khalid; Dr. Zainab Ali (الرياضة المعاصرة, 2022)
It is important to study history as it provides us with solutions to contemporary problems in the light of past experiences, and to study the negatives and positives of these solutions, and based on the principle that people with visual disabilities are a human energy that must be invested in order to serve the progress and prosperity of society, it is important to shed light on this category and contribute to conveying an honorable image of it. it may be a motive for others who were stopped by the extinguishing of the ray of light and insight from completing their lives for a spark of hope that would restore their passion for life, and the study aims to: Document the emergence of goalball for the blind Iraqi Paralympic Games, and document the formation of players and the administrative and technical staff of the Iraqi national team goal ball for the blind men advanced in the Asian championships For the period (2014-2022), documenting the participation and achievements of the Iraqi team with the blind men’s goalball advanced in the Asian championships for the period (2014-2022), and critiquing and analyzing the participation and achievements of the Iraqi team with the blind men’s goalball advanced in the Asian championships for the period (2014-2022), and identifying. The most important reasons and obstacles that prevented the Iraqi team from achieving advanced results in the Asian championships with the goal ball for the blind men. The two researchers adopted the historical inferential approach, based on the results obtained for the participation of the goal football team for the blind men, the advanced category in the Asian championships for the period from 2014 AD until 2022 AD, in order to fit this approach and the objectives of the study.  The target is for the blind men, the advanced category, and a number of coaches and administrators in the Iraqi Federation for the Blind Goal for the Blind. The two researchers reviewed a number of scientific references in the field of the history of physical education, sports for people with disabilities and visual impairment, as well as studies and research related to writing the theoretical framework for the study, in addition to newspapers and magazines. IBSA and the Paralympic Federation for West Asia WAPF, in addition to that, personal interviews were relied on with the players participating in the Asian Championships for the period (2014-2022), and a number of federation administrators according to an unregulated questionnaire, prepared by the two researchers aimed at organizing and classifying questions in a scientific manner.  To get acquainted with the information related to the problem of the study, as well as to identify the most important reasons and obstacles that prevented the achievement of advanced results in some of the specific Asian championships under study. The researchers concluded in the light of the results obtained from the study: that the participation of the advanced men’s goal soccer team in the Asian regional tournaments is at the required level, since competition with teams that have a long history in this sport with better capabilities, and that the participation of the advanced men’s goal soccer team has achieved a high achievement. The team won gold and silver medals in the three West Asian tournaments, because the team’s players had experience in competing at the level of the teams participating in this tournament, and the availability of logistical aspects represented by the support, capabilities and efforts made by the players of the goal soccer team for the blind men, the advanced category and the device  Administrative and technical, as well as the appropriate choice in time and place, the involvement of the team's players in the internal and external camps, all of this contributed to achieving advanced positions and high achievement. In light of the findings of the two researchers, the most important recommendations came: the need to analyze and critique the participation and achievements of teams with visual disabilities in various sports, an analysis based on the scientific methodology, because any development we seek in any field, we must  Standing on the most important positives and trying to make a greater effort, and the failure to achieve the advanced and required level, calls us to identify the most important obstacles and reasons that prevented the achievement of the required level and high achievement, and then try to find appropriate solutions to them, and the need to increase interest in the sport of people with visual disabilities, as they are They consider a creative human energy that contributes to the progress and prosperity of society, the need to pay attention to historical studies of various events and periods of time, as they help us in setting strategic plans and predicting the future, and striving to provide all the requirements of modern training halls, equipment and tools, which contribute to raising the level of training for the blind goal ball to highest possible.